STRATEGI PENGELOLAAN KONFLIK PASANGAN PERKAWINAN CAMPURAN - Prameswari, Wigati Sita; Purnawan, Ni Luh Ramaswati; Suryawati, I Gusti Alit (E-Jurnal Medium, 2019)
ABSTRACT Intercultural marriage is a union between two people who have differencesain nationality and culture as husband and wife, whileabuilding family ties. In mixed marriages that occur between individuals who have different cultural backgrounds, each pair has unique dynamics and challenges that they will undergo. The purpose of this study is to describe style of conflict management on intercultural couples. Conflict management is the process to get compatibility while faced the conflict. This study aims to determine the conflict management strategies carried out by married couples who undergo mixed marriages so that mixed marital couples can maintain in forming a harmonious family. This study uses a qualitative exploratory method based on a purposive technique. Data obtained through interviews and documentation The author uses Miles and Huberman'saInteractive Model data analysis techniques which go through several stages, namely data collection, data reduction, data presentation, andaconclusion drawing. In short; the result of this researchais cultural influences individual's view on looking into things, one of them is conflict.The intercultural marriages are frequently encountered by problems and conflicts potential. One of the causes is the cultural background differences. Communicationacompetence between cultures—intercultural marriage couples can understand the conflict pattern based on cultural differences based on values, habits, paradigms, characters, opinions, principles, language – context differences that sometimes leads to misunderstandingsaand child issues. Managing the conflict, the five mixed marriage couples use a variety of conflict management styles including collaboration, compromise and accommodation. Keywords: Intercultural Marriage, Intercultural Communication, Conflict Strategy